HIV-1 Latency (Current Topics in Microbiology and Immunology,, 2018)
This volume summarizes recent advances in understanding the mechanisms of HIV-1 latency, in characterizing residual viral reservoirs, and in developing targeted interventions to reduce HIV-1 persistence during antiretroviral therapy. Specific chapters address the molecular mechanisms that govern and regulate HIV-1 transcription and latency; assays and technical approaches to quantify viral reservoirs in humans and animal models; the complex interchange between viral reservoirs and the host immune system; computational strategies to model viral reservoir dynamics; and the development of therapeutic approaches that target viral reservoir cells. With contributions from an interdisciplinary group of investigators that cover a broad spectrum of subjects, from molecular virology to proof-of-principle clinical trials, this book is a valuable resource for basic scientists, translational investigators, infectious-disease physicians, individuals living with HIV/AIDS and the general public.